Abnormal Cerebrovascular Reactivity in Patients with Parkinson’s Disease - Carlos Henrique Ferreira Camargo; Eduardo Antunes Martins; Marcos Christiano Lange; Henrique Alvaro Hoffmann; Jissa Jeanete Luciano; Marcelo Rezende Young Blood; Marcelo Derbli Schafranski; Marcelo Machado Ferro; Edmar Miyoshi (Parkinson's Disease)
Background. Orthostatic hypotension (OH) is an important nonmotor manifestation of Parkinson’s disease (PD). Changes in cerebrovascular reactivity may contribute to this manifestation and can be monitored using transcranial Doppler. Objective. To identify possible changes in cerebrovascular reactivity in patients with OH. Methods. Twenty-two individuals were selected and divided into three groups: with and without OH and controls. Transcranial Doppler was used to assess basal mean blood flow velocity, postapnea mean blood flow velocity, percentage increase in mean blood flow velocity, and cerebrovascular reactivity as measured by the breath-holding index. Results. PD patients had lower values of basal velocity (p=0.019), postapnea velocity (p=0.0015), percentage increase in velocity (p=0.039), and breath-holding index (p=0.04) than the controls. Patients with OH had higher values of basal velocity (p=0.09) and postapnea velocity (p=0.19) but lower values of percentage increase in velocity (p=0.22) and breath-holding index (p=0.32) than patients without OH. Conclusions. PD patients present with abnormalities in a compensatory mechanism that regulates cerebral blood flow. OH could be an indicator of these abnormalities.